The Effectiveness of the Kurikulum Cinta Grounded in Social Emotional Learning in Enhancing Students’ Character in Elementary School Hindu Religious Education - I Putu Widyanto; Putu Wisnu Saputra; Raisa Vienlentia; Elsa; Sugita Anayeci (Universitas Pendidikan Ganesha, 2026)
Character education in Hindu Religious Education at elementary schools still faces challenges in systematically integrating character development and social-emotional competencies because learning focuses more on cognitive aspects than meaningful affective and behavioral dimension. This study aimed to evaluate the effectiveness and analyze the acceptance of the Kurikulum Cinta grounded in Social Emotional Learning (SEL) in enhancing students’ character in Hindu Religious Education. The study employed a mixed-methods design involving one Hindu Religious Education teacher and 32 elementary school students. Data were collected through classroom observations, interviews, document analysis, and character assessment instruments that had met content and construct validity requirements, with a reliability coefficient of 0.769. Quantitative data were analyzed descriptively, while qualitative data were interpreted thematically. The Technology Acceptance Model (TAM) was also employed to examine teacher acceptance of the learning model. The findings revealed improvements in students’ learning engagement, emotional awareness, reflective abilities, and respectful attitudes. In addition, the model demonstrated high levels of perceived ease of use (90%), perceived usefulness (88.6%), and acceptance (85%). The study concludes that the Kurikulum Cinta grounded in Social Emotional Learning is effective in strengthening students’ character and provides an applicable instructional framework for integrating character education and social-emotional competencies in elementary Hindu Religious Education.